High sensitivity C-reactive protein and alkaline phosphatase levels in apparently healthy adults of bumiputera and non-bumiputera attending Luyang health clinic in Kota Kinabalu Sabah - Eman Suleiaman Farhad (2016)
C-reactive protein (CRP) is an inflammatory marker considered as a risk factor of cardiovascular diseases. This inflammatory marker was widely studied in research. It was found to be associated with other chronic conditions like metabolic diseases, diabetes type 2 and certain cancers. CRP levels in healthy people of different populations also were highlighted in many studies. However no study was done about the level of this inflammatory marker in Sabah. This cross-sectional study was conducted in Kota Kinabalu, Sabah to assess the level of this marker in healthy people from different races to identify the factors associated with high levels of this marker for early intervention towards health promotion in the community. A total of 232 randomly selected healthy participants were included in this study. The relations of hs-CRP with alkaline phosphatase (ALP) , among different races, as well as different age groups, genders, waist circumferences, basal metabolic rate (BMI), mean arterial pressure (MAP), smoking, marital status and family history of disease were evaluated using multiple regression model. The median for high sensitivity C-reactive protein (hs-CRP) was 1.2 mg/L and higher in males than females 1.2 mg/L, 1.1 mg/L respectively. There was no significant difference in median hs-CRP levels in different races in the study population. A significant correlation between high levels of hs-CRP and ALP was found p <0.001. BMI, MAP, ALP were contributing significantly to the model p <0.001. The odds of high risk hs-CRP> 3 mg/L in females with high BMI was almost 23 times higher as compared with females of normal BMI and four times higher in overweight and obese females in comparison to overweight and obese males. Those with ALP level 1 U/L higher had 5% more odds of having high risk hs-CRP compared to those with lower ALP level and those with 1mmHg higher in MAP had 7% more odds of having high risk hs-CRP. The model explained 36% (Nagelkerke R2) of the variance in high hs-CRP (>3 mg/L) and correctly classified 84% of the cases. In conclusion, this study revealed that BMI, MAP, ALP were independent predictors of high levels of hs-CRP. High levels of hs-CRP were found significantly in overweight and obese which was more obvious in females than males rendering them at higher risk of developing chronic conditions like cardiovascular disease. Further epidemiological studies are suggested.